MAGNETIC ADSORBENT BASED ON CARBOXYMETHYL CELLULOSE FOR METHYLENE BLUE UPTAKE FROM AQUEOUS MEDIA - Tayeb Benhalima1, 2, Amina Sadi1, Hafida Ferfera-Harrar1 (university of eloued جامعة الوادي, 2024)
ross-linked carboxymethyl cellulose/Dextran sulfate (CMC/DS) magnetic nanocomposite beads, incorporating oxide iron nanoparticles (Fe3O4) via ionotropic gelation, were synthesized and characterized using FTIR, SEM/EDX, NanoSEM, XRD, TGA, and VSM. The addition of Fe3O4 imparted a porous structure, enhanced thermal stability, and superparamagnetic properties, facilitating efficient separation through an external magnetic field. Evaluated for methylene blue (MB) adsorption, the nanocomposites exhibited favorable pseudo-second-order kinetics, driven by chemisorption via electrostatic interactions. The Langmuir model described the adsorption isotherms, with a slightly reduced maximum equilibrium capacity (331 mg g-1) compared to the matrix (384 mg g-1). Demonstrating excellent reusability over five cycles, these magnetic nanocomposites present promising prospects for environmental remediation.
Keywords: Carboxymethyl cellulose; Hydrogels; Magnetic nanoparticles; Adsorption; Reuse